Refinement of the Spinal Muscular Atrophy Locus by Genetic and Physical Mapping - Wang, C. H. (1995)
We report the mapping and characterization of 12 microsatellite markers including 11 novel markers. All markers were generated from overlapping YAC clones that span the spinal muscular atrophy (SMA) locus. PCR amplification of 32 overlapping YAC clones shows that 9 of the new markers (those set in italics) map to the interval between the two previous closest flanking markers (D5S629 and D5S557): cen - D5S6 - D5S125 - D5S435 - D5S1407-D5S629-D5S1410-D5S1411/D5S1412-D5S1413-D5S1414-D5Z8-D5Z9-CATT1-D5Z10/D5Z6-D5S557-D5S1408-D5S1409-D5S637-D5S351-MAP1B-tel. Four of these new markers detect multiple loci in and out of the SMA gene region. Genetic analysis of recombinant SMA families indicates that D5S1413 is a new proximal flanking locus for the SMA gene. Interestingly, among the 40 physically mapped loci, the 14 multilocus markers map contiguously to a genomic region that overlaps, and perhaps helps define, the minimum genetic region encompassing the SMA gene(s).